Intranasal Immunization of Mice with Inactivated Virus and Mast Cell Activator C48/80 Elicits Protective Immunity against Influenza H1 but not H5. (April 2014) - Xu, Lili; Bao, Linlin; Li, Fengdi; Lv, Qi; Yuan, Jing; Xu, Yanfeng; Deng, Wei; Yao, Yanfeng; Yu, Pin; Qin, Chuan
<x xml:space="preserve">Abstract</x> Vaccination represents the most economic and effective strategy of preventing influenza pandemics. We previously demonstrated that intranasal immunization of mice with recombinant hemagglutinin and the mast cell activator C48/80 elicited protective immunity against challenge with the 2009 pandemic H1N1 influenza in mice, demonstrating that the novel C48/80 mucosal adjuvant was safe and effective. The present study demonstrated that intranasal immunization with inactivated H1N1 virus and C48/80 elicited protective immunity against lethal challenge with homologous virus, however, when the immunogen was replaced with inactivated H5N1 virus protection was lost. These observations suggested that the adjuvant effects conferred by C48/80 were virus subtype specific and that its use as a broad-spectrum adjuvant for use in immunizations against all influenza viruses needs to be further analyzed.